The Home of the Redwood
On verso: Map showing location of "The Home of Redwood", Panama-Pacific Exposition Grounds, San Francisco 1915. The Home of Redwood is an artistically designed and completely furnished residence built entirely on Redwood. In its interior finish it displays many new and beautiful treatments of the wood. Do not fail to see it.